The coming wave : AI, power and our future - Suleyman, Mustafa, ....-; Bhaskar, Michael, ....- (UK : Vintage, 2024)
Soon you will live surrounded by AIs. In a world of quantum computers, robot assistants and abundant energy, they will organise your life, operate your business, and run government services. None of us are prepared. Mustafa Suleyman has been at the centre of this revolution. The next decade, he explains, will be defined by a wave of powerful, fast-proliferating new technologies. These will create immense prosperity but also present risks. How do we ensure the flourishing of humankind? How do we maintain control over these technologies? And how do we find the narrow path to a successful future? In this groundbreaking book we learn how to think about the essential challenge of our age.
Keywords: AI